A call to action—stopping antimicrobial resistance. Issue 1 (7th January 2023) - Eisinger, Robert W; Williams, Mark P; Choe, Sung Hee; Krofah, Esther
Abstract: Antimicrobial resistance is a public health emergency and represents an impending pandemic. Implementing the lessons learned from responding to the COVID-19 pandemic is essential in accelerating the development of new antimicrobials and therapeutic strategies, rapid diagnostics and improved vaccines. A rededicated, coordinated and collaborative global effort of all stakeholders in academia, healthcare, government agencies, industry, finance and philanthropy is essential to halt the continued spread of antimicrobial resistance and to prevent further morbidity and mortality from drug-resistant pathogens.